Importance and Relevance of the Brazilian Journal of Transplantation for Brazilian Transplantation - Boin, Ilka de Fatima Santana Ferreira; Haddad, Luciana; Ferreira, Gustavo Fernandes (Brazilian Journal of Transplantation, 2024)
The Brazilian Journal of Transplantation, through its activities and commitment to high ethical and academic standards, aims to consolidate itself as a reference in the dissemination of knowledge and scientific advancement in the field of transplants, both nationally and internationally. BJT’s social contribution as a reliable and peer-reviewed dissemination vehicle is undeniable. It reaches the scientific community and the population in general, demystifying the organ donation processes, highlighting the organ distribution model through the national single queue and raising awareness of the need for donation.